Partnership for facilitating sustainable protected area management : a case study of Jiuzhaigou National Park in south-western China : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Yang, Qingxia; Yang, Qingxia (Massey University, 2011)
The number of global protected areas is continuously increasing and nearly 13% of the earth’s land area is now covered by protected areas. How to manage protected areas ― over the long-term and in a sustainable way ― has become critical. The protected area management paradigm has shifted, in order to promote inclusive practices, such as the involvement (and thus the participation) of multiple stakeholders within management. This participation is about the local community, tour operators, research agencies, NGOs and government agencies working in partnership. However, what partnership actually means in practice is not so easily understood. Using a case study approach, this thesis examines three different partnerships within a Chinese National Park ― Jiuzhaigou National Park ― in order to provide a thorough understanding of partnership in practice, within the context of the sustainable management of protected areas. This thesis concludes that partnership is important for the facilitation of management of protected areas in a sustainable way. However, in practice, partnership does not necessarily have to be strong in all the areas of partnership principles. The partners in this study are not really sharing power in regards to decision-making but, nevertheless, these particular partnerships demonstrate three positive elements: the stakeholders hold a strongly shared goal that is compatible with the management objectives for protected areas; the stakeholders hold different resources that can be pooled to achieve the shared goal; and stakeholders perceive and gain mutual benefits, through working together. It is suggested, however, that an effective protected area partnership should consider the role of mutual transparency, accountability, trust, respect and influence. These key elements would further strengthen harmony within the relationship between the partners and, as a result, it would lead to more desirable long term management and sustainable outcomes for protected areas.
Keywords: Management stakeholders; National park management; Sustainable protection